Communication as Instrument of Expansion in Small and Medium Spanish Companies: The Segovian Case - Gómez Nieto, Begoña (2011)
Implementation and development of communicative strategies is still incipient in the Spanish SME’s market. Companies keep using old techniques instead of moving forward on innovative plans due to the lack of knowledge regarding the effectiveness of new programs.